JURNAL REVIEW: PERANCANGAN APLIKASI UNTUK PROTOKOL KESEHATAN DIMASA PANDEMI COVID-19 - Imam Yunianto; Muhamad Malik Mutoffar (Institut Bisnis Muhammadiyah Bekasi, 2021)
The Covid 19 epidemic which lasted more than one year resulted in the issuance of instructions from the ministry of home affairs to implement the Enforcement of Community Activity Restrictions (PPKM) and the enforcement of the 5 M health protocol, which included wearing masks, maintaining distance and checking body temperature. However, there are still people who do not follow the discipline. For that we need supervision that can monitor community activities. Research that has been carried out by previous researchers can replace human supervision which is limited by the amount and time. From previous research, there are also obstacles from making the application. This study aims to find a reasech gap from previous research, so that it can make research that can continue previous research and improve the weaknesses of previous research.